Illegal wildlife trade as the leading cause of orphaned pangolin and vervet monkey arrival to the Lilongwe Wildlife Centre - Battoo, Ishwinder; Hart, Lynette A. (Frontiers in Conservation Science, 2025)
Illegal wildlife trade (IWT) is a major driver of biodiversity loss, threatening countless species, including pangolins (Pholidota: Manidae) and vervet monkeys (Chlorocebus pygerythrus). This study analyzed causes of admission, medical findings, and outcomes of orphaned pangolins and vervet monkeys at the Lilongwe Wildlife Centre (LWC) in Malawi from 2019–2023 to understand the impact of these species’ common threats. Medical records of 83 orphaned animals (34 pangolins, 49 vervets) were reviewed. Chi-squared tests assessed associations between variables. IWT was the primary cause of admission for pangolins (97.1%) and vervet monkeys (53.1%). Pangolins confiscated from IWT often presented as dehydrated (48.5%), underweight (42.4%), and lethargic (27.3%), with necropsies frequently revealing pneumonia (83.3%) and gastric ulcers (50%). Top pangolin outcomes included death (36.4%) and release (30.3%). Vervets admitted from IWT were either ex-pets or intercepted while being sold as pets or bushmeat. Ex-pets all exhibited unremarkable physical exams, while intercepted vervets often displayed injuries from rope (38.5%) and malnourishment (23.1%). Top vervet outcomes included remaining in care at LWC (80.8%) and release (7.7%). Admissions of both species peaked during the months of September through February, aligning closely with breeding cycles and the hot, wet season (November-April). This study highlights the main threats these species face and underscores the need for targeted conservation strategies to mitigate these threats. Understanding clinical trends and causes of admission can inform rescue, rehabilitation, and release efforts, contributing to the conservation of these ecologically vital species.